'Staff-resident relationships in approved premises: What a difference a door makes': A practitioner response. (December 2017) - Doggett, Laura
This piece is a response to Irwin-Rogers' (2017) article 'Staff-resident relationships in approved premises: What a difference a door makes', in which the impact of the staff office door policies on staff-resident relationships in approved premises is highlighted. The findings of Irwin-Rogers will be discussed, alongside the importance of staff-offender relationships, the benefits of a psychologically informed approach and consideration for what is needed to support staff working in approved premises (AP) to work effectively with this often challenging and emotionally demanding client group.